SINTESIS DAN UJI AKTIVITAS ANTIBAKTERI SENYAWA KALKON TERHADAP BAKTERI KONTAMINAN PRODUK DARAH GRAM NEGATIF DAN POSITIF - Wiwit Sepvianti; Christiyani Kusumaningrum, Serafica Btari (Akademi Farmasi Indonesia Yogyakarta, 2022)
Background: The development of chalcone-based antibiotics has been widely carried out today, variations in the location and type of functional groups were carried out to find chalcone with the best bacterial inhibitory activity. However, the obstacle faced was that not all variations of chalcone showed good bacterial inhibitory activity. The trend of increasing or decreasing antibacterial activity due to variations in the location and type of substituent in chalcone is difficult to detect, because comparative data on the inhibitory activity of chalcone are not current or are no longer relevant to current conditions where the test bacteria have mutation as a form of adaptation or resistance to antibiotics. Objective: This research was conducted to provide current data on the antibacterial activity of chalcone against gram-positive and gram-negative bacteria. Methods: Chalcone was synthesized by Claisen-Schmidt condensation and activity test by diffusion method. Results: The yield of chalcone obtained in this study was 96.15%, with the percent purity based on the results of GC-MS was 100%. Inhibitory activity of chalcone on gram-negative bacteria Escherichia coli is in the strong category with an inhibitory value of 81.30% while Acinetobacter is weak with a percentage of 43.0%. In gram-positive bacteria Staphylococcus aureus the inhibitory ability is moderate with a percentage of 64.0%, while in Staphylococcus epidermidis and Bacillus sp the inhibitory activity is weak with a percentage of 35.5% and 43.0%, respectively. Conclusion: Chalcone have strong activity on Gram-negative bacteria and tend to be moderate on Gram-positive bacteria.